Modified Archad’s Equation to Estimate Wear Volume due to Sliding Speed - Yusuf Kaelani; Bisma A Permana (JMES: The International Journal of Mechanical Engineering and Sciences, 2021)
The objective of this research is to introduce a mathematical model of wear volume of Archard’s equation influenced by speed variable. Some researchers have studied the wear volume due to sliding speed, roughness and coefficient of friction. However, mathematical model dealing with sliding speed has never been explicitly reported. Wear analysis is oftenly expressed experimentally through charts concerning both wear volume and sliding speed instead of mathematics. This research is started by modeling mathematical representation within Buckingham Pi Theory. The mathematical parameter contains wear volume, hardness, normal loads, sliding speed, sliding distance, and density of materials. Buckingham Pi model produces three sets of equation. Two of these sets yields Archard’s equation. By combining the third set, the modified Archard’s equation is determined. Since Buckingham set requires a constant of equality, the equation is verified by experiment data. This value is called Wear-Speed Coefficient. Experiment using pin-on-disk tribometer is conducted by varying sliding speed. Further more, those parameters are applied to estimate wear volumes. Materials which are used for this verification are NBR Rubber Nitril, Ultra High Molecular Weight Poly Ethylene (UHMWPE), and Poly Tetra Fluoro Ethylene (PTFE). In conclusion, the modified Archard equation is determined to estimate wear volumes. Based on the experiment, the model is accurate for UHMWPE, NBR and PTFE. Moreover, ratio of density to material’s hardness is significant to control wear resistance influenced by speed.